Hubungan Terpaan Iklan Pada Akun Instagram @bukalapak dan Online Customer Review dengan Keputusan Pembelian Online di Bukalapak - Raihan Wiguna, Ilham; Setyabudi, Djoko; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Bukalapak is one of Indonesia's leading local marketplaces, facilitating online transactions for millions of sellers and buyers. The company actively engages in marketing activities through Instagram ads to attract target consumers and encourage purchase decisions. Additionally, online customer reviews (OCR) are crucial for potential buyers in marketplace. The research problem is the relationship between Instagram ads and OCR with online purchase decisions at Bukalapak. This study uses a quantitative explanatory approach. The study aims to determine the relationship between Instagram ads on @bukalapak and OCR with online purchase decisions at Bukalapak. The theories used are strong advertising theory and Buyer Information Environment Theory. The sample consists of 100 respondents aged 16-64 who have been exposed to ads on Instagram @bukalapak and have seen OCR on Bukalapak from March to April 2024. The sampling technique used is nonprobability sampling, and data analysis is conducted using Kendall's Tau B test. The results show a positive relationship between Instagram ads on @bukalapak and online purchase decisions at Bukalapak, with a significance value of 0.000. Additionally, the relationship between OCR and online purchase decisions at Bukalapak is also significant, with a significance value of 0.000. The conclusion is that both Instagram ads on @bukalapak and OCR have a relationship with online purchase decisions at Bukalapak.